MEASUREMENT OF NO2 INDOOR AND OUTDOOR CONCENTRATIONS IN SELECTED PUBLIC SCHOOLS OF LAHORE USING PASSIVE SAMPLER - T. Mehmood; Z. Ali; N. Noor; S. Sidra; Z.A Nasir; I. Colbeck (Journal of Animal and Plant Sciences, 2015)
Higher levels of NO are a danger to human health especially for children. A seven day study was carried to find out the 2 ambient concentrations of NO in 27 schools of Lahore with the help of passive samplers. In each school three sites were 2 selected, viz: laboratory, corridor and outdoors. After 7 days exposure the tubes were subjected to spectrophotometric 3 analysis. Results showed that the maximum values measured in laboratory, outdoor and corridors were 376µg/m , 3 3 3 3 3 222µg/m and 77µg/m . Minimum values for laboratory, outdoor and corridors were 10µg/m , 20µg/m and 8µg/m . Factors affecting these values were laboratory activities and proximity to main roads. These values were significantly higher than the standard values defined by EPA. Therefore children in schools were at risk of developing health complications. and its reported levels were much higher than the
Keywords: Nitrogen dioxide; Lahore; passive samplers; schools; spectrophotometric analysis